State of the Art of Geopolymers: A Review - Droguett-Villalobos, T (Walter de Gruyter GmbH, 2022)
Geopolymers emerge as an ecological alternative for construction materials. These consist of a mixture of aluminosilicate sources and an alkaline solution that dissolves the silicon and aluminum monomers that come from the source to generate a gel called N-A-S-H that will control the main properties of the geopolymer. The geopolymer stands out for having good resistance to compression, as well as good resistance to high temperatures and corrosive environments. They have great potential as a replacement for classical technologies such as concrete, however, require further applied research to determine their feasibility on an industrial scale. © 2022 Hengels Castillo et al., published by De Gruyter.